Educational mobility in developing countries - Florencia Torche (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
This paper reviews the small but growing literature on intergenerational educational mobility in the developing world. Education is a critical determinant of economic well-being, and it predicts a range of non-pecuniary outcomes such as marriage, fertility, health, crime, and political attitudes. We show that developing nations feature stronger intergenerational educational persistence than high-income countries, in spite of substantial educational expansion in the last decades. We consider variations in mobility across gender and region, and discuss the macro-level correlates of educational mobility in developing countries. The paper also discusses the literatures on (i) concepts and measures of educational mobility, (ii) theoretical perspectives to understand educational persistence across generations, (iii) the role that education plays in the economic mobility process, and (iv) differences in the type and quality of education as vehicles for intergenerational persistence, and it applies these literatures to understand educational mobility in the developing world.
Keywords: 330; Educational mobility; developing countries; educational expansion; private schools; gender differences in education; equality of opportunity; economic development